Design and fabrication of modified bi-layer poly vinyl alcohol adhesive sealant film for preventing gastrointestinal leakage - Dorkhani, Erfan; Noorafkan, Yasmin; Asbagh, Reza Akbari; Okhovat, Maryam; Heirani-Tabasi, Asieh; Ahmadi Tafti, Seyed Mohsen (Frontiers in Surgery, 2022)
Anastomosis leakage is a common complication in gastrointestinal surgery associated with high mortality, morbidity, and cost to health care providers. According to the significant burdens of AL, several methods have been introduced to overcome this problem. Despite the crucial complications of the AL, current approaches, including glue-based adhesives and bio-based sealants, have certain disadvantages and newly gained attractions for solving this challenge. This study focused on fabricating a sealant structure based on poly ( vinyl alcohol) film patterned with gelatin particles and evaluating for prevention of AL. Here, we used a 3D printed model for dry spraying gelatin particles in a random and oriented pattern on PVA films. The mechanical and adhesion properties of both types of films were assessed further, and the efficacy of the novel sealant was evaluated in vivo. The results revealed that the film with an oriented pattern provided better adhesive and mechanical properties, expression of anti-inflammatory cytokines, and collagen deposition. In conclusion, our novel sealant enhanced mechanical features and the healing process of gastrointestinal surgical anastomosis and can be considered a novel method for the prevention of AL.